Answer :
Answer:
[tex]y=mx+(y_1-mx_1), b=y_1-mx_1[/tex]
Step-by-step explanation:
The point slope form of the equation of a line is given as:
[tex]y-y_1=m(x-x_1)[/tex]
The slope-intercept form of the equation of a line is given as:
[tex]y=mx+b[/tex]
where: m=slope, b=y-intercept.
To convert from the point slope form to slope intercept form, follow these steps:
Step 1: Distribute the right hand side
[tex]y-y_1=m(x-x_1)\\y-y_1=mx-mx_1[/tex]
Step 2: Isolate the y variable
[tex]y=mx-mx_1+y_1\\y=mx+(y_1-mx_1)[/tex]
This is the slope-intercept form. We can evaluate [tex]y_1-mx_1 $ given values for $(x_1,y_1)$ and slope, m[/tex]